Strategy and Development Plan Strategy and Development Plan of Croatian Transport and Economic System ... - Miloš, Ivan; Maras, Dubravka; Filipčić, Ivan (Promet - Traffic&Transportation)
The Republic of Croatia, as well as many transition countries,is facing a number of difficulties in the field of transport,economy, foreign trade and foreign exchange transactions, externaland internal debt, social policy, demography, etc. In orderto solve these extremely complex problems it is necessary todetermine a strategy and an implementation plan of special instrumentsincluded in the state economic policy of the developmentof transport and economy. Until now the results haveshown that the implementation of conventional instrumentscannot lead to satisfactory results. One of the instruments of thecentral state economic policy - recognised internationally andmost frequently used instruments for solving the mentionedproblems without state investment and state risk - is the instituteof ’Free Zone’. The aim of this work is to help governmentauthorities and bodies to accept possibly quicker and more efficientsolutions to the actual problems by elaborating special instrumentsof state transport and economic policy and by proposingmeasures for their implementation in the Republic ofCroatia. Moreover, it invites professionals and scientists to contributethrough their expert knowledge in finding out new solutions.